Sistem Informasi Manajemen Perpustakaan Berbasis AI Menggunakan Collaborative Filtering Untuk Rekomendasi Buku Otomatis Di Perpustakaan Mamuju - Indah, Asmi Nur; Fitriyana, Aida; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
The development of artificial intelligence (AI) technology shows great potential in supporting the transformation of digital information services, including in library system management. Modern libraries are required to be able to provide services that are fast, personalized, and adaptive to user needs. This study aims to design the concept of an AI-based Library Management Information System using the Collaborative Filtering method as an automatic book recommendation system at the Mamuju Library. The research method uses a systematic literature study approach by analyzing 32 relevant national and international articles to identify implementation patterns, system architecture models, and the resulting benefits. The results of the study indicate that the application of Collaborative Filtering can increase the accuracy of recommendations and the effectiveness of book searches by up to 40–75% based on comparative studies that have been conducted in various digital libraries. In addition, the use of AI has been proven to improve the user experience, accelerate the information retrieval process, and support data-based decision-making by librarians. The proposed conceptual model consists of three main components: the library system database, the AI recommendation engine, and the user interface.